AMELOBLASTOMA INCIDENCE IN CHILDREN : A SCOPING REVIEW - Yolanda Pratiwi; Williyanti Suwondo; Harmas Yazid Yusuf (Universitas Pahlawan Tuanku Tambusai, 2024)
Ameloblastoma is a benign tumor originating from odontogenic epithelial, slow growth and locally invasive. Ameloblastoma rarely occurred in children. Ameloblastoma in Western countries was estimated around 8.7 – 15%, meanwhile in Asia African countries the incidence was around 14.6 – 25%. This study aims to discover the incidence of ameloblastoma in children. This is a literature review study using scoping review approach and applying PRISMA ScR (Preferred Reporting Items for Systematic Reviews and Meta Analyses-Scoping Review) approach on searches utilizing Boolean Operators on databases PubMed, Science Direct, Sage Journals, and EBSCOhost with pre-arranged keywords using PCC framework, with keywords “((Ameloblastoma) AND (Pediatric) OR (Ameloblastoma) AND (Children))”. Total 11 articles eligible in this study. Ameloblastoma incidence in children was about 10 – 15%, where 11 – 18% occurred in children aged 14.7-year-old. The highest mean age was reported in Jordan with mean 16.0-year-old, while the lowest mean age was in Argentine with mean 10.8-year-old. The Incidence of ameloblastoma in children was about 10-15% based on eleven articles that have been identified using different sample collection techniques.